Exploring the components and mechanism of Solanum nigrum L. for colon cancer treatment based on network pharmacology and molecular docking - Chen, Jin-Fang; Wu, Shi-Wei; Shi, Zi-Man; Qu, Yan-Jie; Ding, Min-Rui; Hu, Bing (Frontiers in Oncology, 2023)
Background: Solanum nigrum L. (SNL) (Longkui) is a Chinese herb that can be used to treat colon cancer. The present study explored the components and mechanism of SNL in treating colon cancer by using network pharmacology and molecular docking. The binding efficiency of the main active components of SNL to the key target proteins was verified by cellular thermal shift assay (CETSA). Methods: The components of SNL were collected from TCMSP, ETCM, HERB, and NPASS databases. Meanwhile, the target proteins of these ingredients were collected/predicted by TCMSP, SEA, SwissTargetPrediction, and the STITCH databases. CC-related target genes were identified from TCGA and GTEx database. The interaction networks were established by via Cytoscape 3.7.2. Gene Ontology (GO) and KEGG pathways were enriched by using the David 6.8 online tool. Finally, the binding of key components and targets were verified by molecular docking, and the CETSA was used to detect the efficiency of apigenin and kaempferol binding to AURKB protein in CT26 cells. Results: A total of 37 SNL components, 796 SNL targets, 5,356 colon cancer genes, and 241 shared targets of SNL and colon cancer were identified. A total of 43 key targets were obtained through topology analysis. These key targets are involved in multiple biological processes, such as signal transduction, response to drug and protein phosphorylation. At the same time, 104 signaling pathways, such as pathways in cancer, human cytomegalovirus infection and PI3K-Akt signaling pathway, are also involved. The binding of the four key components (i.e., quercetin, apigenin, kaempferol, and luteolin) and the key targets was verified by molecular docking. The CETSA results showed that apigenin and kaempferol were able to bind to the AURKB protein to exert anti-CRC effects. Conclusions: Quercetin, apigenin, kaempferol, and luteolin are the main components of SNL in treating colon cancer. SNL regulates multiple bioprocesses via signaling pathways, such as pathways in cancer, PI3K-Akt and cell cycle signaling pathway.